2017
DOI: 10.1142/s0219455417500390
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Response Control of a Mindlin-Type Beam

Abstract: Optimal boundary control for damping the vibrations in a Mindlin-type beam is considered. Wellposedness and controllability of the system are investigated. A maximum principle is introduced and optimal control function is obtained by means of maximum principle. Also, by using maximum principle, control problem is reduced to solving a system of partial differential equations including state, adjoint variables, which are subject to initial, boundary and terminal conditions. The solution of the system is obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Mathematically, there are two parts in the braces in Equation (5). The first part is In Figure 5, it was found that the maximum value of the control moment increased sharply when decreasing the probe radius; in Figure 6, when increasing the flexoelectric patch thickness, the control moment increased.…”
Section: The Flexoelectric Control Momentmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematically, there are two parts in the braces in Equation (5). The first part is In Figure 5, it was found that the maximum value of the control moment increased sharply when decreasing the probe radius; in Figure 6, when increasing the flexoelectric patch thickness, the control moment increased.…”
Section: The Flexoelectric Control Momentmentioning
confidence: 99%
“…Mathematically, there are two parts in the braces in Equation (5). The first part is dependent on both the probe radius and patch thickness, and the second part is dependent on the probe radius only.…”
Section: The Flexoelectric Control Momentmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the work of Bernstein (1995) and Tyan and Bernstein (1995), the two types of controllers are combined through the performance index of piecewise function. The optimal nonlinear control law is then derived using Pontryagin's maximum principles (Yildirim, 2016; Yildirim and Kucuk, 2016; Yildirim et al., 2016).…”
Section: Optimally Saturated Nonlinear Constraint Control Lawmentioning
confidence: 99%
“…The original contribution to literature is that the present paper is dealing with the vibration control by maximum principle of a Timoshenko beam, modeled as an equation including the derivatives of the state variable with respect to the time variable at the fourth order. The extended version of this work is to be published in [6].…”
Section: Introductionmentioning
confidence: 99%